KETERKAITAN SELF REGULATED LEARNING DAN SELF EFFICACY TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SERTA DAMPAKNYA PADA REPRESENTASI MATEMATIS SISWA - Wulandari, Merysa; Sri Anggoro, Bambang; Dinda Pratiwi, Dona (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between self-regulated learning and self-efficacy on the ability to understand mathematical concepts and their impact on mathematical representation abilities. The method used in this study is a quantitative approach with ex-post facto. The sample in this study consisted of upper-level students selected using a proportional random sampling technique. Data collection was carried out through questionnaires for self-regulated learning and self-efficacy as well as tests to measure conceptual understanding and mathematical representation abilities. Data analysis in this study used path analysis. The results of this study illustrate that self-regulated learning and self-efficacy have a significant positive impact on conceptual understanding abilities. In addition, conceptual understanding also has a significant impact on the ability to perform mathematical representation. Self-regulated learning and self-efficacy also have an indirect influence on mathematical representation abilities through conceptual understanding. These findings demonstrate the importance of strengthening self-regulated learning and self-confidence in the mathematics learning process to improve students' conceptual understanding and mathematical representation abilities.